Young People as Consumers of Information Technology in a Third World Country - Shaikh, Mohammad Asim; Shaikh, Mohammad Adil; Asar, Farzana (Nurture, 2012)
Governments, Parents and teachers need to act as facilitators and mediators in the process of adoption and shaping of media culture rather than either acting as passive onlookers or active controllers Review of available observations and Assessment of impacts of ICTs on lives of young people in developing countries on the basis of experts views and relevant information. This study reviewed the situation and tried to explore the views and practices of young people belonging to a developing country through a small sample survey. This survey was conducted in Karachi, the most urbanized city of Pakistan. A questionnaire was used to explore the views and practices of young people belonging to a developing country through a small sample survey. Students from two colleges were randomly selected to fill the questionnaires. Most of the ICT resources were used more often by boys. Majority of respondents did not felt hat it had made significant impact on their work or family life. Most of them felt that it had made appositive impact on their lives this survey revealed that majority of college students were wer satisfied with their use of ICT resources.